Twenty-eight day repeated exposure of human 3D bronchial epithelial model to heated tobacco aerosols indicates decreased toxicological responses compared to cigarette smoke - Chapman, Fiona; Pour, Sarah Jean; Wieczorek, Roman; Trelles Sticken, Edgar; Budde, Jessica; Röwer, Karin; Otte, Sandra; Mason, Elizabeth; Czekala, Lukasz; Nahde, Thomas; O’Connell, Grant; Simms, Liam; et al. (Frontiers in Toxicology, 2023)
Tobacco harm reduction (THR) involves providing adult smokers with potentially reduced harm modes of nicotine delivery as alternatives to smoking combustible cigarettes. Heated tobacco products (HTPs) form a category with THR potential due to their ability to deliver nicotine and flavours through heating, not burning, tobacco. By eliminating burning, heated tobacco does not produce smoke but an aerosol which contains fewer and lower levels of harmful chemicals compared to cigarette smoke. In this study we assessed the in vitro toxicological profiles of two prototype HTPs’ aerosols compared to the 1R6F reference cigarette using the 3D human (bronchial) MucilAirTM model. To increase consumer relevance, whole aerosol/ smoke exposures were delivered repeatedly across a 28 day period (16, 32, or 48 puffs per exposure). Cytotoxicity (LDH secretion), histology (Alcian Blue/ H&E; Muc5AC; FoxJ1 staining), cilia active area and beat frequency and inflammatory marker (IL-6; IL-8; MMP-1; MMP-3; MMP-9; TNFα) levels were assessed. Diluted 1R6F smoke consistently induced greater and earlier effects compared to the prototype HTP aerosols across the endpoints, and in a puff dependent manner. Although some significant changes across the endpoints were induced by exposure to the HTPs, these were substantially less pronounced and less frequently observed, with apparent adaptive responses occurring over the experimental period. Furthermore, these differences between the two product categories were observed at a greater dilution (and generally lower nicotine delivery range) for 1R6F (1R6F smoke diluted 1/14, HTP aerosols diluted 1/2, with air). Overall, the findings demonstrate the THR potential of the prototype HTPs through demonstrated substantial reductions in toxicological outcomes in in vitro 3D human lung models.